Pharmacophylogenetic relationships of genus Dracocephalum and its related genera based on multifaceted analysis - Liu, Haolin; Feng, Xiaowei; Zhao, Yulian; Lv, Guoshuai; Zhang, Chunhong; Aruhan,; Damba, Tsend-Ayush; Zhang, Na; Hao, Dacheng; Li, Minhui (Frontiers in Pharmacology, 2024)
The Lamiaceae genus Dracocephalum, with over 30 species, is believed to have considerable medicinal properties and is widely used in Eurasian ethnomedicine. Numerous studies have researched on the geographical distribution, metabolite identification, and bioactivity of Dracocephalum species, especially amidst debates concerning the taxonomy of its closely related genera Hyssopus and Lallemantia. These discussions present an opportunity for pharmacophylogenetic studies of these medicinal plants. In this review, we collated extensive literature and data to present a multifaceted view of the geographical distribution, phylogenetics, phytometabolites and chemodiversity, ethnopharmacological uses, and pharmacological activities of Dracocephalum, Hyssopus, and Lallemantia. We found that these genera were concentrated in Europe, with species adapted to various climatic zones. These genera shared close phylogenetic relationships, with Dracocephalum and Hyssopus displaying intertwined patterns in the phylogenetic tree. Our review assessed more than 900 metabolites from these three genera, with terpenoids and flavonoids being the most abundant. Researchers have recently identified novel metabolites within Dracocephalum, expanding our understanding of its chemical constituents. Ethnopharmacologically, these genera have been traditionally used for treating respiratory , liver and gall bladder diseases. Extracts and metabolites from these genera exhibit a range of pharmacological activities such as hepatoprotective, anti-inflammation, antimicrobial action, anti-hyperlipidaemia, and anti-tumour properties. By integrating phylogenetic analyses with network pharmacology, we explored the intrinsic links between metabolite profiles, traditional efficacy, and modern pharmacology of Dracocephalum and its related genera. This study contributes to the discovery of potential medicinal value from closely related species of Dracocephalum and aids in the development and sustainable use of medicinal plant resources.